How big can a walking fish be? A theoretical inference based on observations on four land‐dwelling fish genera of South Vietnam. Issue 5 (10th November 2021) - KUZNETSOV, Alexander N.
Abstract: Comparative study of terrestrial locomotion of 4 fish genera including Anabas, Channa, Clarias, and Monopterus, was performed in experimental setting with the substrate surface of wet clay. No special adaptations for terrestrial locomotion were found. Every fish uses for propulsion on land what it already has. Eel‐shaped Monopterus crawls by body undulations in a serpentine or sidewinding technique, the latter of which was not previously observed beyond snakes. The other 3 fish genera walk by body oscillations using stiff appendages as propulsors. When they are located anteriorly, as the serrate operculum in Anabas and the preaxial spine of the pectoral fin in Clarias, the propulsion is termed prolocomotor, when posteriorly, as the spiny anal fin in Channa —metalocomotor. Channa is the heaviest fish walking out of water in our days, quite comparable in size with first Devonian tetrapods Acanthostega and Tulerpeton . A theoretical calculation is suggested for the upper size limit of a fish capable of terrestrial walking without special locomotor adaptations. It should be roughly 20 cm in the vertical dimension of the trunk, which is just a little above the known size of Devonian tetrapodomorph fishes Panderichthys and Elpistostege . The metalocomotor walking technique of Channa is suggested as the closest extant model for terrestrial locomotion at the fish‐tetrapod transition. The major difference is that the metalocomotor propulsor in Channa is represented by the anal fin, while in tetrapodomorphs by the pelvic fins. The sprawled pelvic fins were advantageous in respect of reduced requirement for side‐to‐side tail swinging. Abstract : Modern amphibiotic fishes use various walking techniques but are smaller in length than half a meter, whereas extinct tetrapodomorph fishes of Devonian ranged from 0.5 to 2.5 m. Could they walk out of water, and how did they walk if they could? This study argues that, in recent ichthyofauna, snakehead is most appropriate for modeling walking technique of tetrapodomorph fishes, and provides calculation that their size was at the upper limit for a walking fish.